Ethics in information technology - Reynolds, George (Course Technology Cangage Learning, 2010)
Ethics in Information Technology, 3e, International Edition is a highly anticipated revision that will help readers understand the legal, ethical, and societal implications of information technology. The third edition offers updated and newsworthy coverage of issues such as file sharing, infringement of intellectual property, security risks, Internet crime, identity theft, employee surveillance, privacy, compliance, social networking, and ethics of IT corporations. This book offers an excellent foundation in ethical decision-making for current and future business managers and IT professionals